Phylogenetic regionalization of tree assemblages reveals novel patterns of evolutionary affinities in the Atlantic Forest. (16th December 2020) - Rezende, Vanessa Leite; Pontara, Vanessa; Bueno, Marcelo Leandro; van den Berg, Eduardo; Silva de Miranda, Pedro Luiz; de Oliveira‐Filho, Ary Teixeira; Dexter, Kyle G.
Abstract: Aim: We used a phylogenetic approach to group assemblages of woody plant into major vegetation units in the Atlantic Forest, thus for the first time incorporating information on species evolutionary relationships into a bioregionalization of this critical hotspot. A phylogenetic regionalization will provide a spatially explicit framework for answering many basic and applied questions in biogeography, ecology and conservation. Location: Atlantic Forest. Taxon: Angiosperms Methods: Our data set comprises 614 genera and 116 families, spread over 1, 755 assemblages. To place assemblages in a multivariate evolutionary composition space, we used a phylogenetically informed ordination analysis, and to determine what the main phylogenetic groups of assemblages were, we used K‐means clustering based on phylogenetic dissimilarity of assemblages. To quantify how well environmental variables distinguish the phylogenetic groups found, we implemented classification tree approaches. Then, to explore the evolutionary turnover between the phylogenetic groups, we calculated phylogenetic beta diversity. Finally, we determined the lineages that are most strongly associated with individual phylogenetic groups using an indicator analysis for lineages. Results: Our analyses suggest that there are seven principal groups, in terms of evolutionary lineage composition, in the Atlantic Forest. The greatest turnover of phylogenetic lineage composition separates tropical evergreen rain forest and semideciduous assemblages from subtropical and highland assemblages. The mixed subtropical forest showed the lowest phylogenetic compositional similarity values with other groups. Tropical rain forest had the highest number of significant indicator lineages, and the highest values of the indicator statistic for lineages. Main conclusions: We found that the most pronounced evolutionary division separates southern and highland tree assemblages from those occurring under more tropical climates and at lower elevations. Our phylogenetic analyses point to an environmentally driven compositional division, likely based on the regular occurrence of freezing versus non‐freezing temperatures. Precipitation and edaphic regimes that assemblages experience had less definitive effects on their evolutionary lineage composition.